Let's evaluate each of the equations one by one:
a) \(1 + 1 = 1 \times 1\)
- Left side: \(1 + 1 = 2\)
- Right side: \(1 \times 1 = 1\)
- Not true (2 ≠ 1)
b) \(7 \times 1 = 0 + 7\)
- Left side: \(7 \times 1 = 7\)
- Right side: \(0 + 7 = 7\)
- True (7 = 7)
c) \(3 + 1 = 3 \times 0\)
- Left side: \(3 + 1 = 4\)
- Right side: \(3 \times 0 = 0\)
- Not true (4 ≠ 0)
d) \(6 \times 1 \times 0 = 6 + 1 + 0\)
- Left side: \(6 \times 1 \times 0 = 0\)
- Right side: \(6 + 1 + 0 = 7\)
- Not true (0 ≠ 7)
Therefore, the only true equation is b) \(7 \times 1 = 0 + 7\).